Impact from tourism on the economy during the pandemic time - Kovalska , L. V.; Tkachenko , T. I. (Man and Environment. Issues of Neoecology, 2022)
Purpose. Determination of the impact from tourism on the economic, social and natural environment, as well as the role of the tourism industry on the world economy, Ukrainin economics, in particular, within of the Ivano-Frankivsk region.Methods. Statistical, methods of analysis, synthesis, graphic and logical generalization methods.Results. We compared the GDP in terms of the world and the national economics both in percentage and quantitative (conditional units) indicators. To analyze the role of the tourism industry in the world and UA economics, the quantitative indicators for tourist expenses and the income of the tourist business are given. The reason was identified and the changes in the numbers of employees, involved in tourism during 2019-2020 are presented. The main donor countries and recipient countries of tourists were highlighted. The tourist market in the Ivano-Frankivsk region was analysed as of September 1, 2020. The market of tourist services in the world during the Covid-19 pandemic has undergone significant transformations, which were noted both in the reduction of job numbers in the tourism business and in the reductions of the GDP indicator, profit in tourism and expenses by tourism service consumers. The demand on the tourist market was analyzed using the example of the main tourist magnet – the Bukovel resort – Ivano-Frankivsk region. It has been established that the development of tourism in Ivano-Frankivsk region is facilitated by grant programs, namely, the Program for supporting the initiative of local Carpathian communitiesConcluions. The national tourist market directed its activities to meet the needs of domestic tourists. The Bukovel resort remaines the main tourist magnet in Ivano-Frankivsk region. Further development of the tourism business, in particular, within Ukraine, will depend on state investments and grant programs, both national and international ones.